Predictors of anxiety and depression among newly diagnosed people living with HIV: A longitudinal study - Garrido Hernansaiz, Helena; Alonso Tapia, Jesús (My University, 2020)
.

This longitudinal study examined whether past resilience and internalized stigma predicted anxiety and depression among newly diagnosed Spanishspeaking people living with HIV (PLWH). We also analyzed whether coping strategies mediated this relationship. Data were collected at two time points from 119 PLWH. Approximately a third of participants had scores indicative of anxiety symptoms, the same result was found for depressive symptoms. Structural equations modeling revealed that 61% of the variance of anxiety and 48% of the variance of depression 8 months after diagnosis was explained by the proposed model, which yielded a good fit to data. Anxiety and depressive symptoms were significantly and negatively predicted by positive thinking, thinking avoidance, and past resilience, and positively predicted by self-blame. Additionally, anxiety was positively predicted by internalized stigma. Past resilience negatively predicted internalized stigma, self-blame, and thinking avoidance and it positively predicted positive thinking. Internalized stigma positively predicted self-blame. Moreover, internalized stigma had a significant indirect effect on anxiety symptoms through self-blame, and past resilience had significant indirect effects on anxiety symptoms and depressive symptoms through internalized stigma and coping. The results point to the need for clinicians and policy makers to conduct systematic assessments and implement interventions to reduce internalized stigma and train people living with HIV to identify and use certain coping behaviors.
Artículos en revistas